Quantum Control of Coherent π-Electron Dynamics in Aromatic Ring Molecules - Mineo, Hirobumi; Phan, Ngoc-Loan; Fujimura, Yuichi (Frontiers in Physics, 2021)
Herein we review a theoretical study of unidirectional π-electron rotation in aromatic ring molecules, which originates from a pair of quasi-degenerate electronic excited states coherently excited by a linearly polarized ultraviolet/visible laser with a properly designed photon polarization direction. Analytical expressions for coherent π-electron angular momentum, ring current and ring current induced-magnetic field are derived in the quantum chemical molecular orbital (MO) theory. The time evolution of the angular momentum and that of the current are expressed by using the density matrix method within Markov approximation or by solving the time-dependent Schrodinger equation. In this review we present the results of the following quantum control scenarios after a fundamental theoretical description of coherent angular momentum, ring current and ring current-induced magnetic field: first, two-dimensional coherent π-electron dynamics in a non-planar (P)-2,2’-biphenol molecule; second, localization of the coherent π-electron ring current to a designated benzene ring in polycyclic aromatic hydrocarbons; third, unidirectional π-electron rotations in low-symmetry aromatic ring molecules based on the dynamic Stark shift of two relevant excited states that form a degenerate state using the non-resonant ultraviolet lasers. The magnetic fields induced by the coherent π-electron ring currents are also estimated, and the position dependence of the magnetic fluxes is demonstrated.